Collaborative networks for a sustainable world 11th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2010, St. Etienne, France, October 11-13, 2010, proceedings - IFIP TC5 WG5.5 Working Conference on Virtual Enterprises (IFIP Advances in information and communication technology, 2010)
Collaborative Networks for a Sustainable World Aiming to reach a sustainable world calls for a wider collaboration among multiple stakeholders from different origins, as the changes needed for sustainability exceed the capacity and capability of any individual actor. In recent years there has been a growing awareness both in the political sphere and in civil society including the business sectors, on the importance of sustainability. Therefore, this is an important and timely research issue, not only in terms of systems design but also as an effort to brow and integrate contributions from different disciplines when designing and/or governing those systems. The discipline of collaborative networks especially, which has already emerged in many application sectors, shall play a key role in the implementation of effective sustainability strategies. PRO-VE 2010 focused on sharing knowledge and experiences as well as identifying directions for further research and development in this area. The conference dressed models, infrastructures, support tools, and governance principles developed for collaborative networks, as important resources to support multi-stakeholder sustainable developments. Furthermore, the challenges of this theme open new research directions for CNs. PRO-VE 2010 held in St. Sustainability cases - I - Sustainability cases - II - Innovation networks - Carbon efficient value networks - Management of CNs in humanitarian organizations - I - Management of CNs in humanitarian organizations - II - Collaborative networks implementations - Collaborative health networks - Networking structures - Partners selection and VO creation – I - Partners selection and VO creation - II - Modeling and managing Competencies - I -- Modeling and Managing competencies - II - Trust and information - Service orientation in collaborative networks - I - Service orientation in collaborative networks - II - Collaboration process models - Performance and value - I - Performance and value - II - Collaborative work environments - Learning and collaboration - Virtual communities and teams - Inter-organisational information systems for CNs – I - Inter-organisational information systems for CNs - II - Semantic interoperability for VO - I - Semantic interoperability for VO - II - Game Theory for CN.